2018
DOI: 10.1186/s12913-018-3833-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety of in-hospital care for acute medical patients at weekends: a qualitative study

Abstract: BackgroundThe increased mortality risk associated with weekend admission to hospital (the ‘weekend effect’) has been reported across many health systems. More recently research has focused on causal mechanisms. Variations in the organisation and delivery of in-hospital care between weekends and weekdays have been identified, but this is not always to the detriment of weekend admissions, and the impact on mortality is uncertain. The insights of frontline staff and patients have been neglected. This article repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…The paucity of published literature on quantitatively measured patient satisfaction is surprising,37 as patient’s, carer’s, and service provider’s experience must be at the centre of the design and delivery of health services. We will fill in these important evidence gaps through our companion framework synthesis, and other components of the HiSLAC project 94–97…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of published literature on quantitatively measured patient satisfaction is surprising,37 as patient’s, carer’s, and service provider’s experience must be at the centre of the design and delivery of health services. We will fill in these important evidence gaps through our companion framework synthesis, and other components of the HiSLAC project 94–97…”
Section: Discussionmentioning
confidence: 99%
“…Após a leitura dos títulos e resumos foram selecionados 54 para a leitura na íntegra, sendo 24 eleitos para participação desta revisão. Apesar dos resultados encontrados, a literatura sugere que a ciência e a prática da segurança do paciente apresentam uma tendência a focar menos nos danos do passado, obtidos através dos estudos retrospectivos e passou a preocupar-se mais na compreensão dos fatores que apoiam o cuidado seguro e a resiliências dos sistemas e serviços de saúde 13 .…”
Section: Resultsunclassified
“…It is now recognised that temporal variation results, at least in part, from delivery models of care and the cultural values of the health-care sector, enshrined in everyday practice, funding models, staffing practices and wider policies. 29 Recent research, such as the High-Intensity Specialist-Led Acute Care study, 30,31 have taken this approach to examine the intensity of specialist-led care in emergency medical admissions, focusing particularly on the organisation and delivery of care, and medical staffing. 30,31 In the case of urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing, 32,33 including in London's hyperacute stroke unit (HASU) model.…”
Section: Chapter 1 Contextmentioning
confidence: 99%
“…29 Recent research, such as the High-Intensity Specialist-Led Acute Care study, 30,31 have taken this approach to examine the intensity of specialist-led care in emergency medical admissions, focusing particularly on the organisation and delivery of care, and medical staffing. 30,31 In the case of urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing, 32,33 including in London's hyperacute stroke unit (HASU) model. 34 However, there has been no large-scale, organisational research to understand what creates temporal in consistency, particularly in services that aim to operate consistently over 7 days, such as the London stroke services.…”
Section: Chapter 1 Contextmentioning
confidence: 99%